Race, media, and the crisis of civil society : from Watts to Rodney King - Jacobs, Ronald N. (Cambridge cultural social studies., 2000)
Comparing African-American and mainstream US newspaper coverage of some of the most important racial crises of the post-war period, this text argues that a strong African-American press is still needed today.